Mesenchymal stem cell-mediated reversal of bronchopulmonary dysplasia and associated pulmonary hypertension - Hansmann, Georg (Medknow Publications & Media Pvt Ltd, 2012)
Clinical trials have failed to demonstrate an effective preventative or therapeutic strategy for bronchopulmonary dysplasia (BPD), a multifactorial chronic lung disease in preterm infants frequently complicated by pulmonary hypertension (PH). Mesenchymal stem cells (MSCs) and their secreted components have been shown to prevent BPD and pulmonary fibrosis in rodent models. We hypothesized that treatment with conditioned media (CM) from cultured mouse bone marrow-derived MSCs could reverse hyperoxia-induced BPD and PH. Newborn mice were exposed to hyperoxia (FiO(2)=0.75) for two weeks, were then treated with one intravenous dose of CM from either MSCs or primary mouse lung fibroblasts (MLFs), and placed in room air for two to four weeks. Histological analysis of lungs harvested at four weeks of age was performed to determine the degree of alveolar injury, blood vessel number, and vascular remodeling. At age six weeks, pulmonary artery pressure (PA acceleration time) and right ventricular hypertrophy (RVH; RV wall thickness) were assessed by echocardiography, and pulmonary function tests were conducted. When compared to MLF-CM, a single dose of MSC-CM-treatment (1) reversed the hyperoxia-induced parenchymal fibrosis and peripheral PA devascularization (pruning), (2) partially reversed alveolar injury, (3) normalized lung function (airway resistance, dynamic lung compliance), (4) fully reversed the moderate PH and RVH, and (5) attenuated peripheral PA muscularization associated with hyperoxia-induced BPD. Reversal of key features of hyperoxia-induced BPD and its long-term adverse effects on lung function can be achieved by a single intravenous dose of MSC-CM, thereby pointing toward a new therapeutic intervention for chronic lung diseases.